Islam as a Religion of Tolerance and Dialogue: A Critical Appraisal - Elius, Mohammad (Journal for the study of religions and ideologies, 2019)
This study analyses Islam as a religion of tolerance and dialogue based on textual analysis and historical interpretation of the Qur'an and Sunnah. It also supports its case by exploring the behaviour of early Muslim rulers towards those belonging to other religions. The study highlights that Islam plays a unique role in promoting religious tolerance and dialogue by providing freedom, justice and equal rights for all irrespective of their religion, culture and civilisation. Though some Qur'anic verses and the Prophetic traditions seem to be contradictory to dialogue and tolerance, upon examination, they are contextualised to particular contexts and circumstances. The study concludes that the teachings of the Qur'an, the Prophetic traditions and the treatment of early Muslim rulers support that Islam plays a vital role in promoting tolerance, dialogue and interreligious harmony in the world.